The role of nurses within the context of indigenous assistance: a literature review (Research, Society and Development, 2021)
Objective: To define the role of nursing professionals regarding assignments within the indigenous context. Methods: It is an exploratory descriptive study, in which the methodology chosen was Integrative Literature Review, searched in the databases of virtual libraries such as: Scielo (Scidentific Eletrônica Library Online), Lilacs (Latin American and Caribbean Literature in Sciences of Health), VHL (Virtual Health Library), Medline (Medical Literature Analysis and Retrieval System Online) and Pubmed (U.S. National Library of Medicine [NLM]). Results: The nurse plays a primary role in assisting indigenous health, we observe that to provide this assistance, we encounter certain difficulties, such as access, but, even in the face of the failures in coverage in the context of providing services to the indigenous, since they are found in a delay, professionals play their role  in the best way possible, even though there is often a lack of training on the part of the agencies and ignorance of the cultures of the ethnic groups where they work. Final Considerations: In the unleashing of nursing work, there are several challenges regarding the context of provision in indigenous care. It concludes an importance regarding the improvement in the implementations of the policies in a comprehensive way by the managers of the three spheres when implementing these policies during the assistance to the local community.